2010
DOI: 10.1007/s00521-010-0385-5
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate forecasting: comparison of various architectures of neural networks

Abstract: This paper evaluates the predictive accuracy of neural networks in forecasting exchange rate. The multilayer perceptron (MLP) and radial basis function (RBF) networks with different architectures are used to forecast five exchange rate time series. The results of each prediction are evaluated and compared according to the networks and architectures used. It is found that neural networks can be effectively used in forecasting exchange rate and hence in designing trading strategies. RBF networks performed better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
1
12
0
1
Order By: Relevance
“…In the case of the exchange rate volatility forecasting, Panda and Narasimhan [6] found that Neural Network (NN) has a better exchange rate forecasting performance for not only in-sample but also outof-sample period, compared to the linear regression and random walk models. Other researchers also find a similar result (see, [3], [13], [22]). Although the NN technique has several advantages that distinguish it from the other existing prediction methods, it is a black box learning approach because it cannot interpret the relationship between input and output or deal with uncertainties.…”
Section: Related Worksupporting
confidence: 70%
“…In the case of the exchange rate volatility forecasting, Panda and Narasimhan [6] found that Neural Network (NN) has a better exchange rate forecasting performance for not only in-sample but also outof-sample period, compared to the linear regression and random walk models. Other researchers also find a similar result (see, [3], [13], [22]). Although the NN technique has several advantages that distinguish it from the other existing prediction methods, it is a black box learning approach because it cannot interpret the relationship between input and output or deal with uncertainties.…”
Section: Related Worksupporting
confidence: 70%
“…They concluded that the proposed model improves the forecasting accuracy achieved by traditional hybrid models and also both of the techniques used separately. Leigh, Purvis, and Ragusa () and Zhang and Wu () demonstrated the successful application of ANN in stock markets to improve forecasts; Dhamija and Bhalla () studied a comparison of various ANN architectures for exchange rate forecasting, finding that ANNs can be effectively used in this task; Khashei, Bijari, and Ardali () showed improvements in predictive results when using ANNs embedded with autoregressive models, concluding that the hybrid model obtained better results than an ARIMA model; Dunis and Huang () applied the ANN to forecast the EUR/USD one step ahead by using autoregressive terms as inputs, showing that the ANN performed better out‐of‐sample than in the traditional model for annualized returns; Galeshchuk () compared the ANN's predictive power in 3 currencies (EUR/USD, GBP/USD, and JPY/USD) in daily, monthly, and quarterly terms; Yao and Tan () showed the advantages of using ANN, specifically in capturing the nonlinear component of the exchange rate; Laboissiere, Fernandes, and Lage () proposed the stock price forecasting of Brazilian power distribution companies based on ANNs, finding that the methodology provides very good performance on MAE, MAPE, and RMSE terms. Furthermore, Muzhou et al () showed that the application of a theoretical model called hybrid constructive neural network method (HCNNM) can correctly forecast the price of tungsten and they were also able to validate it statistically as a good forecasting tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tek katmanlı algılayıcının aksine, ÇKA'lar doğrusal olmayan sorunları çözebilir, bu nedenle yaygın kullanımda en popüler yapay sinir ağı türüdür [15]. Bu ÇKA mimari yapısında giriş katmanından, çıkış katmanından ve k adet gizli katman ve her gizli katmanda 2 adet nörondan oluşmaktadır [16]. Çok katmanlı algılayıcıların çalışma yapısı ağın çıkışının hesaplandığı ileriye doğru hesaplama ve ağırlıkların güncellendiği geriye doğru hesaplama olmak üzere iki aşamadan oluşmaktadır [20].…”
Section: çOk Katmanlı Algılayıcı (Multilayer Perceptron)unclassified